Isolation and phytotoxicity of an active fraction and its pure compound (gallic acid) from sun spurge (Euphorbia helioscopia L.) against harmful weeds - Hegab, Momtaz M.; Erdei, László; AbdElgawad, Hamada (Acta Biologica Szegediensis, 2016)
An active fraction (F5) and its derived pure compound (gallic acid) were extracted from aerial parts of sun spurge (Euphorbia helioscopia). Gallic acid was chromatographically isolated and identified based on spectroscopic analysis 1H and 13C NMR. To investigate the phytotoxicity of F5 (0.1%) and gallic acid (0.001%), their effects were studied against 18 test weeds. In this study, we evaluated the alterations in germination percentage (G%) and speed (GS) as well as seedling length (SL), fresh weight (FW) and dry weight (DW). Also, the change in total phenolic content (TPC) and lipid peroxidation in response to treatment were measured. Our results showed variation in the phytotoxic effect of F5 and gallic acid depending upon weed species. Significant reduction of germination and seedling growth by F5 and gallic acid treatment was common for most of weeds and F5 was more toxic than gallic acid. All weed species accumulated polyphenols as a defence system, but it was not enough to prevent plant damage (lipid peroxidation). We concluded that using weed derived phytotoxic fractions (e.g., F5) and pure compounds (e.g., gallic acid) could play an effective role for weed control instead of using harmful chemical herbicides.